Cement-glass composite bricks (CGCB) with interior 3D printed PET-G scaffolding. (15th July 2022) - Małek, Marcin; Grzelak, Krzysztof; Łasica, Waldemar; Jackowski, Mateusz; Kluczyński, Janusz; Szachogłuchowicz, Ireneusz; Torzewski, Janusz; Łuszczek, Jakub
Abstract: The construction industry is a key sector behind the climate change. Not only does it produce enormous amounts of greenhouse gases, but also absorbs tons of natural aggregates irreversibly. Therefore, this study proposes an alternative approach to the climate change problem by producing a cement-glass composite brick (CGCB) with a printed internal scaffold from recycled Polyethylene Terephthalate Glycol (PET-G). This novel construction material, which consists of about 75% of waste glass and 10% of recycled PET-G scaffolding, has a great potential for tackling this problem. The filling mixture itself – cement-glass mortar (CGM) – and ready-made bricks with an internal PET-G scaffolding (3Dhon structure) were tested to verify the accuracy of the assumptions. The scope of this study included mechanical and thermal tests to indicate the properties of the newly manufactured material. The analysis of the results showed that the final CGCB with 3D printed PET-G scaffolding has better thermal properties than CGM as thermal diffusivity (8%) and decreased specific heat (10%). Additionally, significantly reduced flexural strength and compressive strength has been observed (about 30% of both factors) with almost 100% larger strain during compression testing. Graphical abstract: Image 1 Highlights: The thermal diffusivity of samples increased by 10%. The mechanical properties of samples dropped by about 30%. The samples still corresponds to the S3 class, despite mechanical properties dropp.